Can agricultural intensification help attain Sustainable Development Goals? Evidence from Africa and Asia. Issue 5 (4th May 2019) - Dawson, Neil; Martin, Adrian; Camfield, Laura
Abstract: Market-oriented agricultural intensification is a major development strategy, yet its alignment with sustainable development goals (SDGs) is unclear. We apply indicators for SDG 2 (eradicate hunger) regarding income, food production, food security and land tenure to recent intensifications in Rwanda and Laos to reveal their disaggregated impacts. We find while market-oriented intensification may generate poverty reduction, it also exacerbated marginalisation and poverty through various forms of land tenure insecurity. Ethnicity and gender were influential factors in Rwanda, and post-conflict resettlement policies in Laos. We discuss implications for development practice and selection of suitable indicators to reflect the ambition of the SDGs.